Industry in a changing world : special issue of the Industrial development survey for the fourth general conference of UNIDO - United Nations Industrial Development Organization (New York : United Nations, 1983)
The book is a special issue of the Industrial Development Survey for the Fourth General Conference of the UNIDO. Its main aim is to examine structural changes in industry which in turn bring about changes in the global pattern of comparative advantage.
At head of title: "United Nations Industrial Development Organization, Vienna".
"UN doc. no.: ID/CONF.5/2 ID/304".
"United Nations publication sales no.: E.83.II.B.6"--T.p. verso.
Includes bibliographical references.
lje 14/05/2018
Loans
Keywords: Industrialization; Industries; Industries--Social aspects